Extending the informational basis of welfare economics: The case of preference dynamics - Ulrich Witt; Christian Schubert (Max Planck Institute of Economics, 2010)
Normative reasoning in welfare economics and social contract theory usually presumes invariable, context-independent individual preferences. Following recent work particularly in behavioral economics this assumption is difficult to defend. This paper therefore explores what can be said about preferences and their changes from a motivation-theoretic perspective, i.e. by explaining what motivates economic agents in making their choices and what mechanisms of change are at work here. We show that on this basis it is possible to complement social welfare assessments by a differential weighing of different human motivations which is derived from empirically informed foundations rather than from ad hoc arguments.
urn:nbn:de:gbv:27-20110627-162905-0
Keywords: D63; O12; 330; Preference Change; Welfare; Needs; Subsistence Level; Redistribution; Präferenztheorie; Verhaltensökonomik; Motivation; Soziale Wohlfahrtsfunktion